lingerer, a Drosophila gene involved in initiation and termination of copulation, encodes a set of novel cytoplasmic proteins. - Kuniyoshi, Hisato (2002)
In an effort to uncover genetic components underlying the courtship behavior of Drosophila melanogaster, we have characterized a novel gene, lingerer (lig), mutations of which result in abnormal copulation. Males carrying a hypomorphic mutation in lig fail to withdraw their genitalia upon termination of copulation, but display no overt abnormalities in their genitalia. A severe reduction in the dosage of the lig gene causes repeated attempted copulations but no successful copulations. Complete loss of lig function results in lethality during early pupal stages. lig is localized to polytene segment 44A on the second chromosome and encodes three alternatively spliced transcripts that generate two types of 150-kD proteins, Lig-A and Lig-B, differing only at the C terminus. Lig proteins show no similarity to known proteins. However, a set of homologous proteins in mammals suggest that Drosophila Lig belongs to a family of proteins that share five highly conserved domains. Lig is a cytoplasmic protein expressed in the central nervous system (CNS), imaginal discs, and gonads. Lig-A expression is selectively reduced in lig mutants and the ubiquitous supply of this protein at the beginning of metamorphosis restores the copulatory defects of the lig mutant. We propose that lig may act in the nervous system to mediate the control of copulatory organs during courtship.